Klasyfikacja semantyczna rosyjskich i polskich nazw muzyki rozrywkowej - Kowalczyk, Rafał (Studia Rossica Posnaniensia, 2015)
This paper presents a practical application of multifaceted research into the vocabulary of popular music in contemporary Russian and Polish. It contains explanatory notes in the first part and appendixes, i.e. mini Russian-Polish dictionaries, in the second part. Lexical entries are divided into six semantic groups with the following key concepts: jazz, rock, metal, house, techno and trance, which describe the music styles that appeal to popular tastes.